Understanding digital consumer: A review, synthesis, and future research agenda - Sagkaya Gungor, Aysegul; Ozansoy cadirci, Tugce (WILEY, 2022)
In the last 20 years, the proliferation of digital technologies has significantly impacted both businesses' operations and how consumers get information, engage, and buy. Through the analysis of 74 marketing journals, this article identifies the current situation and possible gaps within digital consumer behavior research. By combining bibliometric analysis and machine learning algorithms, the authors have identified key topics in 5-year intervals and their evolution over time. The study results show that digitalization has overreached its original subsistence and has become an essential aspect of mainstream consumption patterns. The study reveals three domains within digital consumer behavior: (1) the use of classical consumption theories and their application to digital context; (2) transactional subjects within consumers' digitalization; and (3) digital marketing's impact on the consumption of specific product groups. Regression-based time series applied to 42 topics discovered by text mining to define possible future research directions. Within 42 topics, significant growth is expected in mobile channel use, sustainable consumption, user-generated content, and social media engagement. In general, the results exhibit a shift from a transactional point of view to a more theoretical and strategic perspective. Possible research gaps are expected to emerge from: (1) the impact of interactive and immersive technologies on consumption practices; (2) the possible outcomes of the pandemic on digital consumption patterns; (3) enhancing brand engagement through consumer-to-consumer interactions; (4) enhancing the understanding on issues like consumer collaboration, consumer trust, and service satisfaction.
Keywords: digital consumers; longitudinal study; machine learning; online consumers; topic modeling; WORD-OF-MOUTH; BRAND COMMUNITY ENGAGEMENT; CUSTOMER-PERCEIVED VALUE; SOCIAL MEDIA; INTERNET BANKING; MOBILE COMMERCE; PURCHASE INTENTION; MARKETING-RESEARCH; PLANNED BEHAVIOR; ACCEPTANCE MODEL; Business & Economics